Theoretical Study of Methane Formation in the Reaction between Methyl Radical and Propanol-2 - Huu Tho, Nguyen; Liem, Nguyen Vo Hieu; Nhu, Nguyen Thi Huynh; Hong, Nguyen Thi; Thanh, Ngo Vo; Sang, Nguyen Xuan (VNU Journal of Science: Natural Sciences and Technology, 2018)
The reaction paths of the reaction between methyl radical and propanol-2 ( i -C 3 H 7 OH) were investigated with the Density Functional Theory at B3LYP/6-311++G(3df,2p) level. There were seven reaction pathways which formed seven products including CH 4 + (CH 3 ) 2 COH, CH 4 + (CH 3 ) 2 CHO, CH 4 + CH 3 CHOHCH 2 , CH 3 OH + CH 3 CHCH 3 , C 2 H 6 + CH 3 CHOH, (CH 3 ) 2 CH-O-CH 3 + H and (CH 3 ) 3 CH + OH. The analysis of the reaction paths and thermokinetic parameters shows that methane could be generated through three different paths. The removing of H-atom from secondary carbon atom in the propanol-2 molecule was the most favourable of these reaction paths. Keywords Methyl, propanol-2, B3LYP, transition state References [1] I. R. Slagle, D. Sarzyński, and D. Gutman, “Kinetics of the reaction between methyl radicals and oxygen atoms between 294 and 900 K,” Journal of Physical Chemistry, 1987. [2] L. Rutz, H. Bockhorn, and J. W. Bozzelli, “Methyl radical and shift reactions with aliphatic and aromatic hydrocarbons: Thermochemical properties, reaction paths and kinetic parameters,” in ACS Division of Fuel Chemistry, Preprints, 2004. [3] N. H. Tho and N. X. Sang, “Theoretical study of the addition and hydrogen abstraction reactions of methyl radical with formaldehyde and hydroxymethylene,” J. Serb. Chem. Soc.; OnLine First - OLF, 2018. [4] D. Ferro-Costas et al., “The Influence of Multiple Conformations and Paths on Rate Constants and Product Branching Ratios. Thermal Decomposition of 1-Propanol Radicals,” Journal of Physical Chemistry A, p. 4790−4800, 2018. [5] M. T. Holtzapple et al., “Biomass Conversion to Mixed Alcohol Fuels Using the MixAlco Process,” Applied Biochemistry and Biotechnology, 1999. [6] C. R. Shen and J. C. Liao, “Metabolic engineering of Escherichia coli for 1-butanol and 1-propanol production via the keto-acid pathways,” Metabolic Engineering, 2008. [7] A. Frassoldati et al., “An experimental and kinetic modeling study of n-propanol and iso-propanol combustion,” Combustion and Flame, vol. 157, pp. 2–16, 2010. [8] M. Z. Jacobson, “Effects of ethanol (E85) versus gasoline vehicles on cancer and mortality in the United States,” Environmental Science and Technology, 2007. [9] P. Gray and A. A. Herod, “Methyl radical reactions with ethanol and deuterated ethanols,” Transactions of the Faraday Society, 1968. [10] Z. F. Xu, J. Park, and M. C. Lin, “Thermal decomposition of ethanol. III. A computational study of the kinetics and mechanism for the CH3+C2H5OH reaction,” Journal of Chemical Physics, 2004. [11] N. H. Tho and D. T. Quang, “Nghiên cứu lý thuyết đường phản ứng của gốc metyl với etanol,” Vietnam Journal of Chemistry, vol. 56, no. 3, pp. 373–378, Jun. 2018. [12] N. H. Tho and N. X. Sang, “Kinetics of the Reaction of Methyl Radical with Methanol,” VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 1DO - 10.25073/2588-1140/vnunst.4725 , Mar. 2018. [13] T. W. Shannon and A. G. Harrison, “The reaction of methyl radicals with methyl alcohol,” Canadian Journal of Chemistry, vol. 41, pp. 2455–2461, 1963. [14] S. L. Peukert and J. V. Michael, “High-temperature shock tube and modeling studies on the reactions of methanol with d-atoms and CH3-radicals,” Journal of Physical Chemistry A, 2013. [15] P. Gray and A. A. Herod, “Methyl radical reactions with isopropanol and methanol, their ethers and their deuterated derivatives,” Transactions of the Faraday Society, 1968. [16] A. D. Becke, “Density functional thermochemistry. I. The effect of the exchange only gradient correction,” Journal of Chemical Physics, vol. 96, p. 2155, 1992. [17] A. D. Becke, “Density-functional thermochemistry. II. The effect of the Perdew-Wang generalized-gradient correlation correction,” The Journal of Chemical Physics, vol. 97, p. 9173, 1992. [18] A. D. Becke, “Density-functional thermochemistry. III. The role of exact exchange,” The Journal of Chemical Physics, vol. 98, p. 5648, 1993. [19] W. Yang, R. G. Parr, and C. Lee, “Various functionals for the kinetic energy density of an atom or molecule,” Physical Review A, vol. 34 (6), pp. 4586–4590, 1986. [20] W. J. Hehre, L. Radom, P. V. R. Schleyer, and J. A. Pople, Ab Initio Molecular Orbital Theory. 1986. [21] M. P. Andersson and P. Uvdal, “New scale factors for harmonic vibrational frequencies using the B3LYP density functional method with the triple-zeta basis set 6-311+G(d,p).,” The journal of physical chemistry. A, vol. 109, pp. 2937–2941, 2005. [22] Frisch, M. J.; Trucks, G. W.; Schlegel, H.B.; Scuseria, G.E.; Robb, M.A.; Cheeseman, J. R., M. Scalmani, G.; Barone, V.; Mennucci, B.; Petersson, G. A.; Nakatsuji, H.; Caricato, J. L. Li, X.; Hratchian, H. P.; Izmaylov, A. F.; Bloino, J.; Zheng, G.; Sonnenberg, T. Hada, M.; Ehara, M.; Toyota, K.; Fukuda, R.; Hasegawa, J.; Ishida, M.; Nakajima, and Y. . et al. Honda, “Gaussian 09 Revision C.01, Gaussian Inc. Wallingford CT.,” Gaussian 09 Revision C.01. 2010. [23] G. Herzberg, Electronic Spectra and Electronic Structure of Polyatomic Molecules. 1966. [24] L. M. Sverdlov, M. A. Kovner, and E. P. Krainov, Vibrational spectra of polyatomic molecules. New York; Chichester; Jerusalem; London: Wiley ; Israel Program for Scientific Translations, 1974. [25] E. Hirota, “Anharmonic potential function and equilibrium structure of methane,” Journal of Molecular Spectroscopy, vol. 77, pp. 213–221, 1979. [26] P. Venkateswarlu and W. Gordy, “Methyl alcohol. II. Molecular structure,” The Journal of Chemical Physics, 1955. [27] E. . B. Goos A.; Ruscic, B., “Extended Third Millennium Ideal Gas and Condensed Phase Thermochemical Database for Combustion with Updates from Active Thermochemical Tables,” http://garfield.chem.elte.hu/Burcat/burcat.html August-2018.